Naringenin inhibits the growth of Dictyostelium and MDCK‐derived cysts in a TRPP2 (polycystin‐2)‐dependent manner. (May 2014) - Waheed, A; Ludtmann, M H R; Pakes, N; Robery, S; Kuspa, A; Dinh, C; Baines, D; Williams, R S B; Carew, M A
<x xml:space="preserve">Abstract</x> Background and Purpose Identifying and characterizing potential new therapeutic agents to target cell proliferation may provide improved treatments for neoplastic disorders such as cancer and polycystic diseases. Experimental Approach We used the simple, tractable biomedical model Dictyostelium to investigate the molecular mechanism of naringenin, a dietary flavonoid with antiproliferative and chemopreventive actions in vitro and in animal models of carcinogenesis. We then translated these results to a mammalian kidney model, Madin‐Darby canine kidney (MDCK) tubule cells, grown in culture and as cysts in a collagen matrix. Key Results Naringenin inhibited Dictyostelium growth, but not development. Screening of a library of random gene knockout mutants identified a mutant lacking TRPP2 (polycystin‐2) that was resistant to the effect of naringenin on growth and random cell movement. TRPP2 is a divalent transient receptor potential cation channel, where mutations in the protein give rise to type 2 autosomal dominant polycystic kidney disease (ADPKD). Naringenin inhibited MDCK cell growth and inhibited cyst growth. Knockdown of TRPP2 levels by siRNA in this model conferred partial resistance to naringenin such that cysts treated with 3 and 10 μM naringenin were larger following TRPP2 knockdown compared with controls. Naringenin did not affect chloride secretion. Conclusions and Implications The action of naringenin on cell growth in the phylogenetically diverse systems of Dictyostelium and mammalian kidney cells, suggests a conserved effect mediated by TRPP2 (polycystin‐2). Further studies will investigate naringenin as a potential new therapeutic agent in ADPKD. Linked Articles This article is part of a themed section on the pharmacology of TRP channels. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2014.171.issue‐10